2016
DOI: 10.7717/peerj.2117
|View full text |Cite
|
Sign up to set email alerts
|

A unique mating strategy without physical contact during fertilization in Bombay Night Frogs (Nyctibatrachus humayuni) with the description of a new form of amplexus and female call

Abstract: Anurans show the highest diversity in reproductive modes of all vertebrate taxa, with a variety of associated breeding behaviours. One striking feature of anuran reproduction is amplexus. During this process, in which the male clasps the female, both individuals’ cloacae are juxtaposed to ensure successful external fertilization. Several types of amplexus have evolved with the diversification of anurans, and secondary loss of amplexus has been reported in a few distantly related taxa. Within Nyctibatrachus, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
(119 reference statements)
0
18
0
Order By: Relevance
“…Species with derived mating behavior without amplexus often lack release calls (e.g., Malagasy frogs in the subfamily Mantellinae; ; but see Willaert et al 2016 for release calls in Nyctibatrachidae), but this subcategory is in general observed across the majority of anuran families. Release calls can differ among closely related species (e.g., Castellano et al 2002a) and have been proposed as a possible taxonomic character (Grenat & Martino 2013).…”
Section: Functional Categories Of Anuran Vocalizationsmentioning
confidence: 99%
“…Species with derived mating behavior without amplexus often lack release calls (e.g., Malagasy frogs in the subfamily Mantellinae; ; but see Willaert et al 2016 for release calls in Nyctibatrachidae), but this subcategory is in general observed across the majority of anuran families. Release calls can differ among closely related species (e.g., Castellano et al 2002a) and have been proposed as a possible taxonomic character (Grenat & Martino 2013).…”
Section: Functional Categories Of Anuran Vocalizationsmentioning
confidence: 99%
“…Our study represents a unique large dataset on amplexus types for anurans, and allows to highlight three amplexus types (loose amplexus, gular amplexus, scapular amplexus) that have been overlooked in key literature references (i.e. Duellman & Trueb, 1986; Wells, 2007; Vitt & Caldwell, 2014; Pough et al ., 2016; Willaert et al, 2016). We hope that further studies about breeding behavior in anurans include detailed observations and descriptions that could reveal novelty aspects associated to diversity of breeding strategies in vertebrates, even in those lineages considered as well studied.…”
Section: Discussionmentioning
confidence: 99%
“…We defined the documented amplexus types (Fig. 1) following Duellman & Trueb (1986) and Willaert et al ., (2016), but also considering the following clarifications: First, in several species it has been reported that the amplexus type might change at the moment of oviposition (e.g. Anomaloglossus bebei and Brachycephalus ephippium ; Bourne et al, 2001, Pombal et al ., 1994; see supplementary material for more examples).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bombay night frog, Nyctibatrachus humayuni (Family: Nyctibatrachidae), is one of the 35 species of night frogs described from India (Garg, Suyesh, Sukesan, & Biju, ). The frog is endemic to montane and submontane streams of the Western Ghats and exhibits unique courtship and breeding behaviour (Gramapurohit, Gosavi, & Phuge, ; Willaert et al, ). The species is sexually dimorphic with females being larger than males.…”
Section: Introductionmentioning
confidence: 99%